Fixed gunfire timing leads to shorter reaction time with higher reliability in block starts - Otsuka, M.; Kurihara, T.; Isaka, T. (New Studies in Athletics, 2017)
The current rules in athletics allow Starters to subjectively determine the length ofthe period between the "set" command and the firing of the gun or other approved auditory signal. However, differences in this interval, which in the study of psychology is called a foreperiod (FP), lead to differences in reaction time (RT) and unfairness between different races. In this study, the authors clarified the difference ofRT under two different FP length conditions: with a fixed timing between the "set" and the "go" Signals and with random variable timings between the two. They found that single average values of whole-body RT and the electromyographic onset of movement in different muscles in five trials were significantly shorter in the fixed condition than those in the variable condition. The single average value of whole-body RT was 109 ± 15 ms in the fixed condition, suggesting that some Sprinters can react in less than 100 ms limit set in the rules (as opposed to starting before the gun). Moreover, small- er individual Standard deviations of these Parameters were observed in the fixed condition. This information will be helpful in reconsidering how Starters should pull the trigger and the IAAF rules pertaining to false starts.